2019
DOI: 10.1101/793885
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Discordant bioinformatic predictions of antimicrobial resistance from whole-genome sequencing data of bacterial isolates: An inter-laboratory study

Abstract: BackgroundAntimicrobial resistance (AMR) poses a threat to public health. Clinical microbiology laboratories typically rely on culturing bacteria for antimicrobial susceptibility testing (AST). As the implementation costs and technical barriers fall, whole-genome sequencing (WGS) has emerged as a 'one-stop' test for epidemiological and predictive AST results. Few published comparisons exist for the myriad analytical pipelines used for predicting AMR. To address this, we performed an inter-laboratory study prov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Using simulated data we demonstrate improved power and false-discovery rate at the single variant level compared with fixed and random effect models, and illustrate this use in practise on antibiotic resistance phenotypes in two species. We show further results which find similar accuracy between new machine-learning and simpler approaches, consistent with previous studies (4,5,24) . Additionally, our approach was able to estimate trait heritability without assuming specific effect size distributions, which are unproven in bacterial populations.…”
Section: Introductionsupporting
confidence: 92%
See 1 more Smart Citation
“…Using simulated data we demonstrate improved power and false-discovery rate at the single variant level compared with fixed and random effect models, and illustrate this use in practise on antibiotic resistance phenotypes in two species. We show further results which find similar accuracy between new machine-learning and simpler approaches, consistent with previous studies (4,5,24) . Additionally, our approach was able to estimate trait heritability without assuming specific effect size distributions, which are unproven in bacterial populations.…”
Section: Introductionsupporting
confidence: 92%
“…Batch differences such as genotyping methods between cohorts exaggerate this problem, so a consistent approach (such as the one we provide here) should be used. Unsurprisingly, curated resistance sets -the result of decades of research -still generally perform better, although even this in silico method loses accuracy between datasets (24) . Less well understood and potentially polygenic phenotypes such as virulence offer an attractive target for our model, as we demonstrated on two Streptococcal pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…As with any system of analysis, appropriate technical requirements need to be instituted to prevent the caveats associated with poor quality sequencing that can lead to low-coverage and lost sequences. Doyle et al [ 146 ] have highlighted the need for quality sequence for clinical diagnostics wherein they showed missed WGS-based antibiotic resistance calls due to short read, low-coverage data. This has led to the push to adopt long-read, and even circular consensus sequencing, which obviate these issues [ 37 , 147–148 ].…”
Section: Whole-genome Sequencing In Bacterial Diagnosticsmentioning
confidence: 99%
“…IncFIB (AP001918) was the most common plasmid Inc type from our study, in line with the observation that IncF plasmids are frequently associated with the dissemination of resistance (49). However, a limitation of our study is that we did not perform phenotypic antimicrobial resistance testing, although Doyle et al (50) reported that only a small proportion of genotypic AMR predictions are discordant with phenotypic results.…”
Section: Discussionmentioning
confidence: 94%